Surgery for intractable temporal lobe epilepsy: experience of a single institution - Kurt, Gökhan; Tönge, Mehmet; Çeltikçi, Emrah; Çapraz, İrem; Serdaroğlu, Ayşe; Bilir, Erhan (The Scientific and Technological Research Council of Turkey, 2014)
Background/aim: In the treatment of epilepsy, encouraging results have been achieved with surgical treatment, especially for temporal lobe epilepsy (TLE). Drug resistance must be diagnosed as early as possible, because the ensuing seizures can be eliminated surgically via temporal lobe surgery in a high percentage (70%-90%) of patients. In this study we share our experience, in a single institution, of surgical treatment of intractable TLE. Materials and methods: Between March 2006 and November 2010 we performed 127 corticoamygdalohippocampectomy (CAH) procedures. All CAN surgical procedures were done as described by Niemeyer's technique. Resection lengths were 4-4.5 cm from the temporal pole. Results: At the end of 24 months, 79.7% (n = 94) patients were still on antiepileptic medications, with 55 of them on a decreased number or dose of drugs, and 20.3 (n = 24) patients were antiepileptic drug-free. Postoperative Engel's classes were 1, 2, and 3 in 87.2%, 5.08%, and 7.6%, respectively. There was no mortality in follow-up, and dysphasia in 1 patient (0.84%) was the only morbidity. Conclusion: In our series we found that the outcome of surgery is associated with careful patient selection, which requires a detailed investigation of the patients. Our final conclusion is that outcome scores are independent of age, pathology, or sex but are dependent on correct patient selection.
WOS: 000343068800025
PubMed ID: 25539559
Keywords: Corticoamygdalohippocampectomy; Epilepsy Surgery; Hippocampal Sclerosis; Mesial Temporal Lobe; Outcome; Temporal Lobectomy